Membangun Konsep Diri Anak Berkebutuhan Khusus - Jumatul sakdiah; Nana Marsiana; Opi Andriani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
most psychic elements plays a role in the development of individual personality is the self concept, which is an overall self-concept self image that includes a person’s perception of himself, feelings, beliefs, and values associated with him. The self concept is an important aspect in a person, in which the self concept is a frame of reference to interact with the environment. When people perceive themselves, give meaning and shape abstraction assessment of him means he showed self-awareness and the ability to get out of myself to see him as he did to the world outside himself.